Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $x\in G$ and $|x|=n<\infty.$ If $n=st$ for some positive integers $s$ and $t$, prove that $|x^s|=t.$

Observe that if we prove that $(x^s)^t=x^{st}$ then $1=x^n=x^{st}=(x^s)^t$ and we are done. We did not prove that $(x^s)^t=x^{st}$ in class and it is another exercise in the book. Is mathematical induction the only way to prove it?

My proof:

Statement: $(x^s)^t=x^{st}$ for all $1\leq s,t\leq n.$

Base Case: Trivially true.

Inductive Hypothesis: Assume that $(x^s)^t=x^{st}$ for all $1\leq s,t\leq n.$

Now consider (also assuming $x^{s+t}=x^sx^t$):

\begin{align} (x^{s+1})^{t+1}\\ &=(x^{s+1})^t x^{s+1}\\ &=(x^sx)^tx^sx\\ &=(x^sxx^sx\cdots x^sx)x^sx\\ &=(x^s)^tx^tx^sx\\ &=x^{st}x^{s+t+1}\\ &=x^{st+s+t+1}\\ &=x^{(s+1)(t+1)} \end{align} So by the principle of mathematical induction the statement is true.

If there are any mistakes please point them out.

share|cite|improve this question
$(x^s)^t = x^sx^s\cdots x^s$ ($t$-many times) $ = (x\ldots x) \cdots (x \ldots x)$ where the $l$ dots represent $s$-many times and the $c$ dots are $t$ many. So just count the $x's$ there are $st$ of them, so $(x^s)^t = x^{st}$ – Deven Ware Aug 29 '12 at 19:09
In fact, there is a mistake in your induction. To be proven in the second step should be that $(x^s)^{t+1}=x^{s(t+1)}$ for all $s$. – akkkk Aug 29 '12 at 19:48
up vote 5 down vote accepted

Others have addressed the main question, so I’ll just comment on your proof that $(x^s)^t=x^{st}$. You’re making it much too hard, and you’re not really taking advantage of induction.

Let $P(t)$ be the statement that $(x^s)^t=x^{st}$ for all $s\ge 1$. Clearly $(x^s)^1=x^s=x^{s\cdot1}$ for all $s$, so $P(1)$ is true. Now suppose that $P(t)$ is true for some $t\ge 1$. Then for any $s\ge 1$ we have

$$\begin{align*} (x^s)^{t+1}&=(x^s)^tx^s\\ &\overset{(*)}=x^{st}x^s\\ &=x^{st+s}\\ &=x^{s(t+1)}\;, \end{align*}$$

where the starred step uses the induction hypothesis $P(t)$. But $(x^s)^{t+1}=x^{s(t+1)}$ is precisely the statement $P(t+1)$, so we’ve shown that $P(t)$ implies $P(t+1)$, and by induction we can conclude that $P(t)$ is true for all $t\ge 1$. That is, for all $t\ge 1$ and for all $s\ge 1$, $(x^s)^t=x^{st}$, which was what you wanted to prove.

share|cite|improve this answer

By definition $|x| = n$ means that $n$ is the smallest nonnegative integer such that $x^n = e$, where $e$ is the identity.

If $|x^s| = u < t$, then $(x^s)^u = x^{su} = e$. Since $u < t$, $su < n$. This contradicts $n$ being smallest such that $x^n = e$.

If $|x^s| = u > t$, then since $t < u$, one has $e \neq (x^s)^t = x^{st} = x^n$. So $x^n \neq e$. This contradicts $|x| = n$.

Every element in a finite group has finite order, since we have shown that $|x^s| < t$ and $|x^s| > t$ is impossible, you must have $|x^s| = t$.

share|cite|improve this answer

I have two extended comments that won't fit in a comment on this site:

1) Are you doing a proof by induction on $s$ or on $t$. You need to fix one and use induction on the other. (Probably induction on $t$ will be easier.) When you do this, the calculations in the induction step will be easier.

2) With the minor fix suggestd in point 1), you have proved that $\left(x^s\right)^t=1$. However, this is not sufficient to conclude that $\left|x^s\right| = t$. You also need to prove that $t$ is the smallest positive integer such that $\left(x^s\right)^t=1$. This probably won't take much work, but it definitely needs to be included in your proof.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.